2010
DOI: 10.3892/mmr.2010.328
|View full text |Cite
|
Sign up to set email alerts
|

20(S)-Ginsenoside Rg3-induced apoptosis in HT-29 colon cancer cells is associated with AMPK signaling pathway

Abstract: Abstract. 20(S)-ginsenoside rg3 [20(S)-rg3)], one of the main constituents isolated from Panax ginseng, has been shown to have an anti-cancer effect and to induce apoptosis by interfering with several signaling pathways. However, the molecular mechanisms of aMP-activated protein kinase (aMPK) associated with apoptosis in HT-29 colon cancer cells remain unclear. in the present study, we investigated whether 20(S)-rg3 exerts an anti-proliferative effect and induces apoptosis by modulating the aMPK signaling path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…Zhou et al (23) showed that ginsenoside Rg3 can inhibit HepG2 cell proliferation by downregulating the expression of VEGF. Yuan et al (24) reported that the protein expression of anti-apoptotic Bcl2 was downregulated and the protein expression of pro-apoptotic P53 was upregulated by 20(S)-ginsenoside Rg3 in HT-29 colon cancer cells. The present study obtained similar results, which showed that P53 was upregulated, and BCL2 and VEGF were downregulated by treatment of the HepG2 cells with ginsenoside Rg3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Zhou et al (23) showed that ginsenoside Rg3 can inhibit HepG2 cell proliferation by downregulating the expression of VEGF. Yuan et al (24) reported that the protein expression of anti-apoptotic Bcl2 was downregulated and the protein expression of pro-apoptotic P53 was upregulated by 20(S)-ginsenoside Rg3 in HT-29 colon cancer cells. The present study obtained similar results, which showed that P53 was upregulated, and BCL2 and VEGF were downregulated by treatment of the HepG2 cells with ginsenoside Rg3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, consistent with limited evidence for caspase activation, when the three cell types were treated with a general caspase inhibitor (zVAD-FMK), zVAD had only a slight effect on cell death induced by the combination of Rg 3 and doxorubicin (Figure 6A), indicating that the cells were primarily dying a caspase-independent cell death. Since we observed little caspase activation, and since Rg 3 has been previously reported to induce caspase activation in the colon cancer cell line HT-29 [52], we tested the Rg 3 and doxorubicin combination in this cell line to see if caspase activation would be more prevalent in this cell type. We were unable to detect either PARP or caspase-3 cleavage in these cells, and zVAD likewise failed to protect the cells from cell death (Figure S8B-C).…”
Section: Resultsmentioning
confidence: 99%
“… 1 , 2 Rg3, one of ginsenosides derived from heat-processed ginseng, was found to be a potent inhibitor of tumor cell growth. 3 , 4 Rg3 induces apoptosis through generation of reactive oxygen species (ROS) in some cancer cells. 5 , 6 In our previous study, Rg3 induced the proteolytic cleavage of caspase-3 and poly(ADP-ribose) polymerase (PARP) in human breast cancer MDA-MD231 cells.…”
Section: Introductionmentioning
confidence: 99%